2020
DOI: 10.1097/ana.0000000000000749
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Study of Postoperative Cognitive Dysfunction in Older Surgical Patients

Abstract: Background: Postoperative cognitive dysfunction (POCD) is a common neurocognitive complication after surgery and anesthesia, particularly in elderly patients. Various studies have suggested genetic risk factors for POCD. The study aimed to detect genome-wide associations of POCD in older patients. Methods: In this prospective observational cohort study, participants aged ≥65 years completed a set of neuropsychological tests before, at 1 week, and 3 months after major noncardiac surgery. Test variables were con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…In genome-wide association studies of POCD, neither Rickenbacher et al [18] nor Heinrich et al [19 ▪▪ ] could find any significant association. However, three genetic variants of the cholinergic receptor muscarinic 2 and 4 (CHRM2 and CHRM4) were associated with the development of POD [19 ▪▪ ].…”
Section: Genetic Markersmentioning
confidence: 91%
“…In genome-wide association studies of POCD, neither Rickenbacher et al [18] nor Heinrich et al [19 ▪▪ ] could find any significant association. However, three genetic variants of the cholinergic receptor muscarinic 2 and 4 (CHRM2 and CHRM4) were associated with the development of POD [19 ▪▪ ].…”
Section: Genetic Markersmentioning
confidence: 91%
“…Postoperative cognitive dysfunction (POCD) is a common neurocognitive complication after surgery in the elderly, and is characterized by functional impairments, such as memory, executive function, direction, emotion, and visual–spatial structural ability [ 1 , 2 ]. According to recent research, elderly people over 65 years were highly likely to have POCD; moreover, the incidence can reach up to 47.6% of patients at one week and 34.2% of patients at three months after surgery [ 3 ]. There are numerous risk factors for POCD, including aging, educational level, inappropriate diet, obesity, anesthesia, surgery, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative cognitive dysfunction (POCD) is a common complication in elderly patients after anesthesia that manifests as memory impairment occurring a few days to weeks after surgery, decreased ability to learn and recall information, reduced concentration, disordered comprehension of language, and diminished decision-making and social adaptation. 1 Some studies suggested that age, hypoxia, hypotension, anesthesia, and surgical trauma can induce POCD. 2 , 3 Some studies also indicated that the inflammatory reaction induced by surgery might influence the occurrence of POCD and that suppressing the inflammatory reaction could reduce the incidence and severity of POCD.…”
Section: Introductionmentioning
confidence: 99%